2011
DOI: 10.1530/rep-10-0445
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of flagellar force generated by a hyperactivated spermatozoon

Abstract: The flagellar force generated by a hyperactivated monkey spermatozoon was evaluated using the resistive force theory applied to the activated (nonhyperactivated) and hyperactivated flagellar waves that were obtained using high-speed video microscopy and digital image processing in order to clarify the mechanism of sperm penetration through the zona pellucida. No difference in the maximum propulsive force, which was parallel to the longitudinal sperm head axis, was found between the activated and hyperactivated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…By using the mZP oscillatory spherical net model in our numerical experiments, we have come to the conclusion that sharp angles are more favorable, particularly π/4 and combinations π/4 and π/12 or π/4 and π/6. In addition to the findings in [40] and our own results, we consider that a lateral contact, i.e. sharp impact angle of spermatozoid collision, provides a larger contact surface between the spermatozoid and ZP which may facilitate receptor recognition between the two contact surfaces leading to a potentially easier penetration mediated predominantly by biochemical mechanisms.…”
Section: The Results and Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…By using the mZP oscillatory spherical net model in our numerical experiments, we have come to the conclusion that sharp angles are more favorable, particularly π/4 and combinations π/4 and π/12 or π/4 and π/6. In addition to the findings in [40] and our own results, we consider that a lateral contact, i.e. sharp impact angle of spermatozoid collision, provides a larger contact surface between the spermatozoid and ZP which may facilitate receptor recognition between the two contact surfaces leading to a potentially easier penetration mediated predominantly by biochemical mechanisms.…”
Section: The Results and Discussionsupporting
confidence: 63%
“…There are articles where it is pointed that the transversal force generated by a spermatozoid is higher than the propulsive force [40,41] indicating that a sharp angle would be more favorable for the penetration. By using the mZP oscillatory spherical net model in our numerical experiments, we have come to the conclusion that sharp angles are more favorable, particularly π/4 and combinations π/4 and π/12 or π/4 and π/6.…”
Section: The Results and Discussionmentioning
confidence: 99%
“…When hyperactivated sperm are immobilized by adhering to a surface, the bending of the midpiece region just proximal to the sperm head can be extremely severe resulting in strong lateral force exerted by the sperm head. Strong lateral movement of the sperm head during hyperactivation has been shown to be important in penetration of the zona pellucida (Ishijima, 2011). Ho et al (2009 showed that the head pivoting motion that accompanies the asymmetric beating in the early stages of beating is necessary for the sperm to detach from the sperm reservoir in the isthmus of the oviduct and also for entry into the upper oviduct.…”
mentioning
confidence: 99%
“…From the computed time-averaged translation and rotation of an egg, the force and torque exerted by the single spermatozoon can be obtained using Stokes’s law of drag. The force and torque by sperm swimming on the zona have been estimated in various species and different settings212223. Our computational method also follows these literatures, but is based on a more accurate numerical scheme.…”
Section: Methodsmentioning
confidence: 99%